Risk factors for gastric metachronous lesions after endoscopic or surgical resection: a systematic review and meta-analysis - Ortigão, Raquel; Figueirôa, Gonçalo; Frazzoni, Leonardo; Pimentel-Nunes, Pedro; Hassan, Cesare; Dinis-Ribeiro, Mário; Fuccio, Lorenzo; Libânio, Diogo (Endoscopy, 2022)
Introduction Metachronous gastric lesions (MGL) are a significant concern after both endoscopic and surgical resection for early gastric cancer. Identification of risk factors for MGL could help to individualize surveillance schedules and potentially reduce the burden of care, but data are inconclusive. We aimed to identify risk factors for MGL and compare the incidence after endoscopic resection (ER) and subtotal gastrectomy.Methods We conducted a systematic review by searching PubMed, ISI, and Scopus, and performed meta-analysis.Results 52 studies were included. Pooled cumulative MGL incidence after ER was 9.3 % (95 % confidence interval [CI] 7.7 % to 11.0 %), significantly higher than after subtotal gastrectomy (1.2 %, 95 %CI 0.5 % to 2.2 %). After adjusting for mean follow-up, predicted MGL at 5 years was 9.5 % after ER and 0.7 % after subtotal gastrectomy. Older age (mean difference 1.08 years, 95 %CI 0.21 to 1.96), male sex (odds ratio [OR] 1.43, 95 %CI 1.22 to 1.66), family history of gastric cancer (OR 1.88, 95 %CI 1.03 to 3.41), synchronous lesions (OR 1.72, 95 %CI 1.30 to 2.28), severe gastric mucosal atrophy (OR 2.77, 95 %CI 1.22 to 6.29), intestinal metaplasia in corpus (OR 3.15, 95 %CI 1.67 to 5.96), persistent Helicobacter pylori infection (OR 2.08, 95 %CI 1.60 to 2.72), and lower pepsinogen I/II ratio (mean difference –0.54, 95 %CI –0.86 to –0.22) were significantly associated with MGL after ER. Index lesion characteristics were not significantly associated with MGL. ER treatment was possible in 83.2 % of 914 MGLs (95 %CI 72.2 to 91.9 %).Conclusion Follow-up schedules should be different after ER and subtotal gastrectomy, and individualized further based on diverse risk factors.